Switchable divergent synthesis in gold-catalyzed difunctionalizations of o-alkynylbenzenesulfonamides with aryldiazonium salts - Li, Jun; Shi, Hongwei; Zhang, Shan; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Organic letters, 2021)
Gold-catalyzed difunctionalizations of o-alkynylbenzenesulfonamides with aryldiazonium salts are reported herein. Upon irradiation with the blue LEDs, benzosultam products were formed via aminoarylation accompanied by the release of N2. Without irradiation, aryldiazonium salts were engaged as efficient electrophiles, facilitating electrophilic deaurations of the vinyl-Au(I) intermediates, followed by tautomerization to give the N-aryl-substituted α-imino (E)-hydrazones. The regioselectivities of 6-endo-dig and 5-exo-dig cyclizations were excellent.
Gesehen am 01.12.2021